Genration of temporal rainfall intensity distribution profiles and storms runoff hydrographs from typical urban catchments in Singapore - Liang, Qiyi (2017)
With numerous irreversible consequences of urbanization, urban infrastructures such as storm drainage system have been designed to drain excess stormwater and ground water from impervious surfaces and to reduce the impact of flood damage caused by surface runoff. The design capacity of storm drainage is usually determined by Rational Formula. With incomplete representations of storms, Rational Formula might not be suitably conservative to determine the peak runoff for drainage design. Numerical approaches have been developed to estimate the peak runoff for storm drain design, but little research has been done to simulate rainfall hyetograph and to estimate the storm runoff in Singapore. This study is sought to simulate temporal rainfall distribution profiles and generate storm runoff hydrograph. There are two types of hydrograph methods - Modified Rational Method and Soil Conservation Service (SCS) Unit Hydrograph Method. They were used to generate the storm runoff hydrograph and determine the peak runoff rates. The results indicated that the peak runoff rates predicted by Modified Rational Method were larger than that of SCS Unit Hydrograph Method and Rational Formula. The peak runoff rates predicted by Modified Rational Method were highly dependent on the time of concentration. A more conservative estimation procedure was developed after this study for drainage design. However, the runoff hydrographs were generated from American based rainfall intensity distribution profiles. These results may not be fully applicable for Singapore’s usage. Hence, further studies are required to generate runoff hydrograph from local rainfall intensity distribution profiles.